Family Focused Therapy for Bipolar Adolescents: Lessons From a Difficult Treatment Case - George, E; Taylor, DO; Goldstein, B; Miklowitz, D (2011)
This paper examines obstacles and challenges encountered in the manualized Family Focused Therapy-A of an adolescent with bipolar disorder. We begin by describing adolescent bipolar disorder and some of the many complications that frequently accompany it. We summarize Family Focused Therapy (FFT-A), an empirically validated treatment approach for bipolar disorder, originally applied to the treatment of adults with bipolar disorder and modified for use with adolescents and their families. We present the details of a difficult treatment case, and examine the factors that led to its suboptimal outcome. We elaborate on ways in which this case would inform future iterations of FFT-A, and suggest future directions for research in this area. © 2011.